Prevalence and risk factors of hepatitis B vaccine non-response in hemodialysis patients: a narrative review - Nordin, Nor A; Sadikan, Muhammad Z; Lambuk, Lidawani; Lambuk, Fatmawati; Noor, Aina AM; Mohamud, Rohimah; Hashim, Nik HHN (The Journal of Infection in Developing Countries, 2026)
Hepatitis B virus (HBV) infection poses a significant threat to public health, with hemodialysis patients facing an exceptionally high risk due to their compromised immune systems and exposure to blood products. While vaccination is the cornerstone of HBV prevention, hemodialysis patients often exhibit inadequate immune responses to the vaccine, jeopardizing their protection. This narrative review comprehensively evaluates the prevalence of non-response to HBV vaccination among hemodialysis patients and identifies associated factors. Drawing on data from various sources, the review analyzes demographics, clinical characteristics, and vaccination protocols to shed light on the critical determinants of vaccine failure. The analysis reveals significant variability in vaccine response rates among hemodialysis patients, with factors such as age, comorbidities, dialysis duration, and nutritional status playing pivotal roles. Additionally, vaccine type, dosage, and administration schedule influence immunogenicity. The findings provide critical insights into optimizing HBV vaccination strategies for hemodialysis non-responders by identifying underlying risk factors, thereby contributing to enhanced public health outcomes.